Persepsi Body Image, Pengetahuan dan Pola Makan terhadap Status Gizi Remaja Putri di Kota Pekalongan - Ida Baroroh; Ana Setyowati (Jurnal Kebidanan Harapan Ibu Pekalongan, 2024)
The development of adolescents aged 11-20 years is characterized by the emergence of hormonal influences which result in physical changes and growth, which is the basis for paying more attention to their body shape. Various methods will be used to get a body shape so that it looks attractive. The effort taken is to limit food intake. Excessive restrictions will affect nutritional status, especially if they are not based on good knowledge. The aim of the research was to determine the perception of body image, knowledge and eating patterns on the nutritional status of young women in Pekalongan City. The research used an analytical observational study with a cross sectional research design. The research population is young women in Pekalongan City. The sampling technique was purposive sampling with a sample size of 50 respondents. The results of the study showed no relationship between body image and nutritional status, there was a significant relationship between knowledge and eating patterns of adolescent girls and the nutritional status of adolescent girls. It is hoped that young women will increase their knowledge and good eating patterns so as to increase the perception of a healthy body image.